Mainstreaming or dilution? Intellectual property and development in WIPO - Nirmalya Syam (South Centre, 2019)
In 2007 Member States of the World Intellectual Property Organization (WIPO) unanimously adopted a set of 45 recommendations which constitute the WIPO Development Agenda. Developing countries sought to give new direction to WIPO through the Development Agenda, away from the pursuit of facilitating and strengthening protection, acquisition and enforcement of intellectual property (IP) rights as an end in itself towards an approach that would be sensitive to the impact of IP on development, both in terms of opportunities as well as costs. This paper explores whether development considerations have been adequately addressed by WIPO since its creation as the United International Bureau for the Protection of Intellectual Property (BIRPI) in the nineteenth century. The paper also analyses whether the implementation of the WIPO Development Agenda adopted in 2007 has shaped the current vision of the WIPO Secretariat and its Member States to address the impact of IP on development; and whether implementation of the Development Agenda has facilitated the use of IP law and policy as a tool that responds to advancing innovation, industrial, health, agricultural, education and other development policies in developing countries. The paper finds that the approach towards IP in WIPO continues to be dominated by a perspective that pursues acquisition, protection, management and enforcement of IP rights as an end in itself. Conflicting interpretations of development orientation have adversely impacted the implementation of the Development Agenda in the spirit in which the developing countries had proposed the Development Agenda. The paper recommends developing countries to undertake cross regional coordination to enhance their level of engagement on IP and development, advance specific suggestions for achieving greater impact on addressing development challenges through specific activities including projects in the areas of technical assistance as well as norm-setting, pursue governance reforms in WIPO to ensure greater representation of developing countries in the decision making bodies of WIPO and in the staff composition of the WIPO Secretariat, amend the WIPO Convention to align its mandate on IP promotion to the development needs and challenges of its Member States and the development goals of the United Nations (UN), and also pursue a review of the relationship between the UN and WIPO as a UN specialized agency in the UN Economic and Social Council.
Keywords: 300; Immaterialgüterrechte; Internationale Organisation; Welt